2021
DOI: 10.1097/md.0000000000026329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout in medical students in China

Abstract: This meta-analysis aimed to estimate the prevalence of burnout among medical students in China. A systematic search from the following electronic databases: China National Knowledge Infrastructure, Wangfang database, VIP database, Chinese biomedical literature database, PubMed, Embase, Web of Science, and Google Scholar was independently conducted by 2 reviewers from inception to September 2019. The data were analyzed using stata software Version 11. Heterogeneity was assessed using I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
3
10
2
2
Order By: Relevance
“…Over time, the study of burnout has gradually extended to college students [ 2 ]. Learning burnout refers to students’ comprehensive performance such as emotional exhaustion, cynicism, and low professional efficacy caused by failure to meet academic requirements [ 3 ]. ‘Emotional exhaustion’ refers to the feeling of being emotionally overstretched and drained.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the study of burnout has gradually extended to college students [ 2 ]. Learning burnout refers to students’ comprehensive performance such as emotional exhaustion, cynicism, and low professional efficacy caused by failure to meet academic requirements [ 3 ]. ‘Emotional exhaustion’ refers to the feeling of being emotionally overstretched and drained.…”
Section: Introductionmentioning
confidence: 99%
“…They can choose their favorite majors, and their learning burnout level is relatively low. [ 32 ] Moreover, the present study demonstrated that the professional identity differed between single-child families and non-single-child families. Students from single-child families have the strong internal motivation and care more about their interest in the occupation.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown that job burnout is widespread in medical students ( 3 ). For example, the prevalence of job burnout among medical students in the United States was reported to be 52.8% ( 4 ), and it ranged from 38.1% to 53.8% for Chinese medical students ( 5 ).…”
Section: Introductionmentioning
confidence: 99%